(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic and its containment measures directly influenced the psychosocial health of individuals and may lead to the emergence or worsening of signs and symptoms of temporomandibular disorders (TMDs). Thus, the objectives of the present study were to evaluate the impact of the pandemic on the signs and symptoms of TMDs and the influence of the new coronavirus infection on these signs and symptoms. This is a cross-sectional observational research with a quantitative and qualitative approach, carried out in the population of the state of Sergipe and the Federal District. Based on the Diagnostic Criteria for Temporomandibular Disorders DC/TMD, individuals responded via Google forms to the DC/TMD Symptom Questionnaire and the DC/TMD Demographics. A total of 244 individuals participated in the study, 123 from the state of Sergipe and 121 from the Federal District. Of these individuals, 70.8% reported pain in the jaw, temple, ear or in front of the ear and 64.2% reported pain in the temporal region in the last 30 days. Habits or manias, such as clenching or grinding teeth and chewing gum, changed the pain of most respondents (50.8%). No significant association (p≥0.05) was found between the DC/TMD Symptom Questionnaire questions and COVID-19 contamination among respondents. Thus, it is suggested that the pandemic may have impacted the signs and symptoms of TMDs in the population of Sergipe and the Federal District, but the infection with the new coronavirus did not influence these signs and symptoms, and no significant difference was found between the individuals who were infected or not.